Metode Ijtihad Kolektif Progresif di Indonesia Sebagai Media Proyeksi Nalar Kemanusiaan - Mukhammad Nur Hadi (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2023)
This study photographed the ijtihad method of two organizations Rumah KitaB Bersama (Rumah KitaB) and the Indonesian Women Ulema Congress (KUPI). The two points examined are the framework of the ijtihad method and the extent to which it can advocate for the rights of women and children. This study is a normative study by utilizing conceptual and philosophical approaches. Rumah KitaB and KUPI have a basic ushuliyyah approach, but differ in the construction of the paradigm and framework of ijtihad. The House of Book makes maqashid al-Islam a medium of dialogue between text and context. When linked to maqashid al-Islam, the text should be read with a critical paradigm while context with a spiritual paradigm. Then, the relationship of text and context should be read with a framework of alignments. Meanwhile, KUPI makes the rules of ushuliyyah and fiqhiyyah as methods elaborated with maqashid ash-sharia and Islamic universal values, such as humanity, justice, equality, interconnectedness, kindness, benefit, nationality, and universality. The main approaches used are mubadalah, makruf, and ultimate justice. This article finds that the ijtihad framework both contribute significantly to the strengthening of women's rights. It proves that both have created a new current of progressive, responsive, and inclusive collective ijtihad methods in Indonesia without having to abandon the classical texts. In fact, they have fought against Indonesia's established collective ijtihad framework but tend to be less responsive to marginal issues.